Analisis Penerapan Prinsip Akuntansi Dan Pengelolaan Keuangan Pada Masjid Di Kecamatan Kotanopan Kabupaten Mandailing Natal (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the application of accounting principles that have been carried out by mosques with mosques that still do not apply accounting principles so that the accountability of their financial statements can be relied upon. This study uses the type of Qualitative Research and Descriptive Approach method, namely analyzing and describing the Application of Accounting Principles and Financial Management in Mosques in Kotanopan District, Mandailing Natal Regency. The data used in this study are primary data and secondary data. The data collection technique is field research with the form of observation interviews, documentation, and content analysis. From this research it is known that the application of accounting principles has a very large influence on the accountability or accountability of the mosque's financial statements. Based on data collected from various sources, it can be seen that the principles that are less considered in making mosque financial reports are the principle of full disclosure and the principle of realization, so that the accountability of mosque financial reports becomes less transparent. Then to account for the mosque's financial statements, the mosque manager has similarities in providing information to the public and interested parties in the mosque's financial statements, but differs in making financial reports.